The Designation of Recreational and Tourist Areas in the Sustainable Management of Rural and Suburban Areas - Bielska, Anna; Borkowski, Andrzej Szymon; Czarnecka, Adrianna; Delnicki, Maciej; Kwiatkowska-Malina, Jolanta; Piotrkowska, Monika (Geomatics and Environmental Engineering, 2023)
This paper presents guidelines for the designation and development of locations for tourism and recreation in the countryside and on the city outskirts. The proposed criteria for designating these areas can be used in the development of strategic and planning documents. Using the METPRET and SWPR methodology in the area of the Mazowieckie Voivodeship, the research allows for the development of proposals to be included in the strategic documents of the voivodeship. These proposals indicated the need to find new areas with the potential for individual short-term tourism and recreation. In uncertain circumstances, an integrated approach to spatial policy is essential as it ensures the ability of urban, suburban, and rural areas to adapt to change and develop sustainably.